Perceptions Of Mbbs Students Regarding The Effectiveness Of Small Group Discussions Versus Large Group Lectures In Human Gross Anatomy: A Cross-Sectional Study At Gomal Medical College, D.I. Khan” - Aman, Shehla; Khan, Sadia Yasir; Iqbal, Anil; Khan, Amir Amanullah; khan, Yusra; Hassan khan, Muhammad; Dawood, Muhammad (Journal of Neonatal Surgery, 2025)
Background : The purpose of the study aims to assess and compare the perceptions of MBBS students regarding the effectiveness of small group discussions versus traditional large group lectures in the subject of Human Gross Anatomy. The findings are intended to provide valuable insights into the suitability and impact of these teaching methodologies in our specific educational setting. Study Design: A Cross sectional study. Setting And Durtion : Department of Anatomy department Gomal Medical College MTI DIK in Jan- July 2025. Materials & methods: Census based cross sectional study conducted on students of 1st year & 2nd year MBBS students in anatomy department Gomal Medical College MTI DIK in July 2025. Students were properly exposed to both formats of teaching i.e SGD & LGF. Study design was census based cross sectional study. Data was collected from the students by the questionnaire (Likert scale based). Results: data was analysed by using SPSS version 23 and was expressed in frequencies & percentages. Students clearly favor small group discussions over traditional lectures and self-directed learning, particularly appreciating the integration of interactive tools such as the Anatomage table and plastinated models.